TINJAUAN HUKUM ISLAM TERHADAP JUAL BELI DREAM CATCHER (Studi pada Pasar Atas Kotabumi, Lampung Utara) - Nurasari, Nurasari (Universitas Khairun, 2024)
Many traders sell dream catchers at Pasar Atas Kotabumi, North Lampung. The existence of buying and selling dream catchers has implications for sharia issues. The purpose of this research is (1) To examine the practice of buying and selling dream catchers in Pasar Atas Kotabumi, North Lampung. (2) To analyze the Islamic law review of the dream catcher sale and purchase agreement at Pasar Atas Kotabumi, North Lampung. The results of the research conclude that (1) The practice of buying and selling dream catchers at Pasar Atas Kotabumi, North Lampung, includes a greeting contract because the buyer makes payment first and then the goods can be owned. According to the results of research conducted by the author at Pasar Atas Kotabumi, North Lampung, the prices of dream catchers vary. Starting from the cheapest price, namely Rp. 40,000.00 up to Rp. 200,000.00. (2) The practice of buying and selling dream catchers in Pasar Atas Kotabumi, North Lampung, from the 7 (seven) sample people I interviewed, for those who believed that dream catchers were to ward off dreams, the law was haram. But for buyers who don't know the history of dream catchers and use these dream catchers only for decoration, the law is permissible.